THE INFLUENCE OF LIFESTYLE, MOTIVATION, PERCEPTION AND ATTITUDE TOWARD THE PURCHASE DECISION OF ECO FRIENDLY ENVIRONMENT STRAW (CASE STUDY ON THE MANAGEMENT STUDENTS OF HASANUDDIN UNIVERSITY) - Rahmawati Resky Amaliah; Jusni Jusni; Abdul Razak Munir (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
This research aims to determine the effect of lifestyle, motivation, perception, and attitude on the decision to purchase environmentally friendly straw products among the postgraduate students of management at the faculty of Economic and Business, Hasanuddin University. The samples as the object of this study consisted of 150 students. The data are analyzed using path analysis with the help of SPSS 25.use in this research is path analysis with the help of SPSS 25. The results of the research indicate that the lifestyle, motivation, perception, and attitude variables positively affect the purchasing decision mediated by purchasing interest, but there are only three variables that do not significantly have an effect on purchasing decisions, i.e. motivation and attitude as well as perception on purchasing interest.